(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2023)
INTRODUCTION: Fast disintegrating tablets (FDTs) are solid dosage forms that disintegrate and dissolve in the mouth without the need for water within a matter of seconds. In the present study, a fast-disintegrating tablet of diclofenac sodium was prepared using WOWTAB (without water) technology, and its in-vitro characters were analyzed to prepare an optimum formulation. MATERIALS AND METHODS: Diclofenac sodium and its reference standard along with other excipients were collected. Softer tablets with hardness ranging from 1.493 to 1.522 kg/cm2 were prepared using Plackett-Burman (PB) design and central composite design (CCD). Various physicochemical parameters and in-vitro quality parameters of formulations were evaluated using standard methods. RESULTS: The disintegration time of the formulations ranged from 76 to 126 seconds. The in-vitro drug release was found to be from 96.31 to 99.94%. The study of contour plot and surface plot indicated that formulation with maltose concentration of 5 mg and mannitol concentration of 90 mg would produce an optimized formulation of diclofenac fast disintegration tablet with a rapid disintegration time of 1.2 to 1.4 minutes and dissolution percent at 30 minutes of 99.5 to 100%. CONCLUSIONS: Diclofenac FDT was prepared based on WOWTAB technology. Formulation containing maltose 5 mg and mannitol 90 mg would be an optimized formulation of diclofenac FDT, with a rapid disintegration time of 1.2 to 1.4 minutes and dissolution percent at 30 minutes of 99.5 to 100 %.